2020
DOI: 10.3390/ijerph17031092
|View full text |Cite
|
Sign up to set email alerts
|

Community-Engaged Air Monitoring to Build Resilience Near the US-Mexico Border

Abstract: Initiated in response to community concerns about high levels of air pollution and asthma, the Imperial County Community Air Monitoring Project was conducted as a collaboration between a community-based organization, a non-governmental environmental health program, and academic researchers. This community-engaged research project aimed to produce real-time, community-level air quality information through the establishment of a community air monitoring network (CAMN) of 40 low-cost particulate matter (PM) monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 30 publications
(35 reference statements)
0
23
0
6
Order By: Relevance
“…In some studies, photographs, diaries and stories were also created by residents to supplement the monitoring data [ 42 , 43 , 49 , 51 , 55 ]. The timescale and extent of the monitoring varied across the studies identified, from mobile sampling over a few days [ 36 ], to maintaining monitoring sites for a number of years [ 41 ]. Residents also led workshops and community meetings, interpreted data findings, and disseminated information to the wider community and other stakeholders [ 31 , 32 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some studies, photographs, diaries and stories were also created by residents to supplement the monitoring data [ 42 , 43 , 49 , 51 , 55 ]. The timescale and extent of the monitoring varied across the studies identified, from mobile sampling over a few days [ 36 ], to maintaining monitoring sites for a number of years [ 41 ]. Residents also led workshops and community meetings, interpreted data findings, and disseminated information to the wider community and other stakeholders [ 31 , 32 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diversity in both the community members and the research team was viewed as a critical to success across some studies, particularly in ensuring it was representative of the local population [ 35 , 43 , 53 , 65 ]. Lastly, financial recognition for the individuals involved and ensuring that community-based organisations received an appropriate share of the funding was also noted as a facilitator [ 39 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that taking a community-based approach to air monitoring in this project increases local environmental health literacy, and provides direct benefits to community partners, such as engaging youth, and increased capacity and knowledge about air quality, data interpretation, and health impacts [36,37]. CCV led an extensive campaign to publicize the Network, presenting information during community events, meetings with school and other local officials, and interviews with news media.…”
Section: Discussionmentioning
confidence: 99%